(untitled) (Journal of Human Sciences, 2018)
The aim of this study is to identify the level of professional maturity of the third grade secondary school students in Sebha. The sample size is 108 students. The criterion of professional maturity is used as a tool for study. The percentage (test) is used as a statistical method. (21%), who have an average professional maturity (51%), while the students have a professional maturity (poor) (28%). The level of maturity at the vocational level Males is higher than females (26% -15%) and the level of maturity in the majors is higher than the scientific specialization (24% -15%). Comparison between the two means, check the hypothesis, which confirms the existence of significant differences due to the variable specialization at the level (0.05), for the benefit of literary specialization. There are no statistically significant differences due to gender.